Determination of Diffusion Coefficients of Nickel and Vanadium into Stainless and Duplex Steel and Titanium - Šárka Vávrová; Martin Švec; Jaromír Moravec; Daniel Klápště (Metals)
When heterogeneous joints are created, problems with the formation of intermetallic phases arise. There are various ways to reduce the formation of intermetallics. One of the ways that is discussed in this article is to use a suitable interlayer of appropriate thickness when forming the joint. A too-thin interlayer does not protect against the formation of brittle intermetallic phases. On the other hand, a too-thick interlayer increases the heterogeneity of the joint and, thus, decreases its useful properties. Within this paper, the formation of diffusion joints between the base material (AISI 304 steel, duplex steel, AISI 316L steel, or titanium grade 2) and the 0.2 mm thick intermediate layer (nickel or vanadium) was studied. Initial diffusion joints were prepared in a Gleeble 3500 machine, and samples for the study of diffusion kinetics were subsequently heat-treated in a vacuum furnace. The result of the research was the determination of specific diffusion parameters of nickel and vanadium into all four tested base materials. The initial diffusion depth (simple heating to the target temperature without holding at this temperature) of nickel was 4.46 µm into duplex steel and 5.48 µm into Ti Gr. 2 at 950 °C. At the same temperature, the initial diffusion depth of vanadium was 14.54 µm into duplex steel and 14.32 µm into Ti Gr. 2. In addition, general equations for the calculation of diffusion coefficients for the mentioned materials in the temperature range of 850 to 1150 °C were established.